Tip‐mould microcontact printing for functionalisation of optical microring resonator. Issue 1 (20th December 2017) - Peserico, Nicola; Castagna, Rossella; Bellieres, Laurent; Rodrigo, Manuel; Melloni, Andrea
Abstract : We present an approach to functionalise optical microring resonators as hybridisation platforms, using tip‐mould reactive microcontact printing process. Derived from reactive microcontact printing using an ad hoc mould of polydimethylsiloxane (PDMS), the method functionalises single microring resonator with a target‐specific capture agent. The authors report the functionalisation of silicon nitride (SiN) 200 μ m diameter microring resonator with single‐strand DNA and the hybridisation detection of 100 nM target analyte, while concurrently monitoring not‐functionalised microring as a control sensor. Results show that the functionalisation approach permits to address single microring resonators with mutual distance lower than 100 μ m with high precision, enabling a better integration of multiple spotting zones on the chip concerning traditional functionalisation procedures.